2018
DOI: 10.3390/genes9040219
|View full text |Cite
|
Sign up to set email alerts
|

Patchoulol Production with Metabolically Engineered Corynebacterium glutamicum

Abstract: Patchoulol is a sesquiterpene alcohol and an important natural product for the perfume industry. Corynebacterium glutamicum is the prominent host for the fermentative production of amino acids with an average annual production volume of ~6 million tons. Due to its robustness and well established large-scale fermentation, C. glutamicum has been engineered for the production of a number of value-added compounds including terpenoids. Both C40 and C50 carotenoids, including the industrially relevant astaxanthin, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 49 publications
1
66
1
Order By: Relevance
“…Furthermore, using plants as a source for producing a sesquiterpene includes slow growth and varying compositions depending on the geographical location and climate conditions. Several studies have been reported using recombinant microbial cells to produce patchoulol with less time and energy consumption (Albertsen et al, 2011; Asadollahi et al, 2008; Henke et al, 2018; Ma et al, 2019). Asadollahi et al (2008) achieved the patchoulol production of 11.5 mg/L from galactose by suppressing ERG9 after introducing a patchoulol synthesis gene in S. cerevisiae .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using plants as a source for producing a sesquiterpene includes slow growth and varying compositions depending on the geographical location and climate conditions. Several studies have been reported using recombinant microbial cells to produce patchoulol with less time and energy consumption (Albertsen et al, 2011; Asadollahi et al, 2008; Henke et al, 2018; Ma et al, 2019). Asadollahi et al (2008) achieved the patchoulol production of 11.5 mg/L from galactose by suppressing ERG9 after introducing a patchoulol synthesis gene in S. cerevisiae .…”
Section: Introductionmentioning
confidence: 99%
“…Patchouli is an aromatic plant with essential oils that is cultivated in the subtropical regions of India, China, and Southeast Asia like Indonesia. Patchouli oil has immense export potential due to its low production costs and high demand in the perfume and cosmetics industry . Usually the production is done in small companies where the equipment does not meet European standards and there are less regulatory oversights.…”
Section: Introductionmentioning
confidence: 99%
“…The model organism C. glutamicum is widely used in biotechnological industry, since it is a workhorse able to produce various compounds with high production titers [106–117], especially the amino acids l ‐glutamate [118–121] and l ‐lysine [122–127]. Globally, amino acids from C. glutamicum are produced in million ton scale [109].…”
Section: Metabolic Engineering Applications Of Crisprimentioning
confidence: 99%